Maxillary Third Molar Tooth Accidentally Displaced in Buccal Space: Report of Two Cases - Kanj Hassan Wasfi; Hassib Nada Wayzani; Georges Aoun; Nicolas Antoine Berberi (Shiraz University of Medical Sciences, 2021)
The extraction of retained and completely impacted third molars is one of the most common surgical procedures performed by dental practitioners with low rates of complications. The accidental displacement during the surgeries of the maxillary third molar into adjacent anatomical spaces is one of the most critical problems that can arise. The most common sites of migration during surgical interventions are the infratemporal fossa, the pterygomandibular space, the maxillary sinus, the buccal space, and the lateral pharyngeal space. In this paper, two cases in which a maxillary third molar accidentally was displaced into the buccal space are presented, the retrieval of the tooth via intra-oral approach is explained, and the anatomical spaces implications are discussed.